Analisis Ward and Peppard Model Pada Strategi Bisnis dan Perencanaan Strategis Sistem Informasi - Daim Azhari Parinduri; Roslina Roslina; Zakarias Situmorang (STMIK Budi Darma, 2021)
Muslim Nusantara Al-Washliyah University is a private university that already has information system technology and information technology as an effort to improve the competitiveness of higher education. However, the existence of the existing information system is still not perfect so that work becomes inefficient. Therefore, this research was conducted to make strategic planning of information systems so as to increase the competitiveness of higher education institutions. The model used in strategic planning in this study is the Ward and Peppard model. The strategic plan is drawn up for a timeframe of 2 phases. The process begins with Internal and External Business Analysis through SWOT Analysis, Value Chain Analysis, PEST Analysis and testing of strategy results using the Profile Matching method which is the choice to provide an assessment of recommended information system applications. There are three aspects in conducting the assessment and evaluation, namely new aspects, develop and continue.